Violence and power in the thought of Hannah Arendt - Ashcroft, Caroline (Intellectual history of the modern age, 2021)
"The book deepens our understanding of Arendt's conception of the role of violence in her political theory. But it also uses her work as a provocation to think about how we might engage with, build on, or criticize contemporary ideas of the political that have drawn on Arendtian themes-notably via the notion of "agonal" or "agonistic" politics as theorized in recent years by thinkers such as Chantal Mouffe and Bonnie Honig-and how we can read Arendt in different ways to challenge or further our understanding of the political"--